Analyzing the Influence of Service Quality towards the Brand Image, Preceived Value, and Brand Loyalty of The Costumers of Heritage Hotel in Malang - Muhammad Iskandar Sjah (Universitas Hayam Wuruk Perbanas, 2018)
Service quality in heritage hotel in the Malang city and brand loyalty have an important role to affect the guests to stay at the hotel, by considering competition in modern time currently. The purpose of this research is to analyze the effect of service quality on brand loyalty, brand image, perceived value, brand image affect brand loyalty, perceived value influence on brand loyalty, and the effect of service quality on brand loyalty which is mediated by brand image and perceived value at Pelangi Hotel Malang. This study uses questionnaires with a total sample of 160 respondents. To get the sample, it uses a purposive sampling. Data were analyzed Â using SPSS (Statistical Package for the Social Science) version 18.0 and Smart Modeling PLS version 2.0. The results of this study indicate that there is a significant-direct effect of service quality on brand loyalty, brand image and perceived value. In addition, brand image also significantly affects brand loyalty. The results also show the effect of perceived value on brand loyalty, and service quality on brand loyalty through brand image and brand loyalty through perceived value.